Target Therapy in Thyroid Cancer: Current Challenge in Clinical Use of Tyrosine Kinase Inhibitors and Management of Side Effects - Puliafito, Ivana; Esposito, Francesca; Prestifilippo, Angela; Marchisotta, Stefania; Sciacca, Dorotea; Vitale, Maria Paola; Giuffrida, Dario (Frontiers in Endocrinology, 2022)
Thyroid cancer (TC) is the most common endocrine malignancy. TC is classified in differentiated thyroid cancer (DTC) that includes papillary and follicular subtypes and Hurthle cell variants, medullary thyroid cancer (MTC), anaplastic thyroid cancer (ATC) and poorly differentiated thyroid cancer (PDTC). Standard of care in DTC consist of surgery together with radioactive iodine (131I) therapy and thyroid hormone; instead, patients with MTC do not benefit from131I therapy. Patients with advanced TC resistant to 131I treatment (RAI-R) had no chance of cure, as well as patient affected by ATC and progressive MTC, in which conventional therapy play only a palliative role, representing, until few years ago, an urgent unmet need. In the last decade, a better understanding of molecular pathways involved in the tumorigenesis of specific histopathological subtypes of TCs has led to develop tyrosine kinase inhibitors (TKIs). TKIs represent a valid treatment in progressive advanced disease and were tested in all subtypes of TC, highlight improving in progression free survival. However, treatments using these novel therapeutics are often accompanied by side effect, that required an optimal manage to minimize their toxicities and thereby enable patients who show benefit to continue treatment and obtain maximal clinical efficacy. The goal of this overview is to provide an update on the current use of the main drugs recently studied for advanced TC and the management of the adverse events.